Senior high school students’ challenges in speaking English across proficiency levels: A narrative inquiry - Shalehah, Ayunda Baqiyatus; Rahmawati, Henny (Universitas Islam Malang, 2025)
This study aims to identify and analyze the challenges Islamic high school students faced in speaking English, focusing on the different levels of speaking ability among students. Using a qualitative approach and narrative research design, the study involved three students with different speaking abilities (high, medium, and low) selected through purposive sampling. Data were collected through semi-structured interviews which took around 10 minutes for each student that revealed various internal and external factors affecting students' speaking ability. The results showed that students faced various difficulties, including lack of confidence, nervousness, vocabulary, limited access to resources, and peer support. In addition, an educational environment that emphasizes religious learning reduces students' opportunities to practice English. Nonetheless, students also developed strategies to overcome these challenges, such as increasing self-confidence and finding study buddies. The findings provide important insights for educators and researchers to design more effective interventions to improve English speaking skills among students of different ability levels. This study is believed to highly contribute to both students and teachers in practice and teaching and as a reference for the future researchers.